Urinary K+ promotes irritative voiding symptoms and pain in the face of urothelial barrier dysfunction - Nicolas Montalbetti (Nature Portfolio, 2019)
Abstract The internal surface of the bladder is lined by the urothelium, a stratified epithelium that forms an impermeable barrier to water and urine constituents. Abnormalities in the urothelial barrier have been described in certain forms of cystitis and were hypothesized to contribute to irritative voiding symptoms and pain by allowing the permeation of urinary K+ into suburothelial tissues, which then alters afferent signaling and smooth muscle function. Here, we examined the mechanisms underlying organ hyperactivity and pain in a model of cystitis caused by adenoviral-mediated expression of claudin-2 (Cldn2), a tight junction protein that forms paracellular pores and increases urothelial permeability. We found that in the presence of a leaky urothelium, intravesical K+ sensitizes bladder afferents and enhances their response to distension. Notably, dietary K+ restriction, a maneuver that reduces urinary K+, prevented the development of pelvic allodynia and inflammation seen in rats expressing Cldn2. Most importantly, intravesical K+ causes and is required to maintain bladder hyperactivity in rats with increased urothelial permeability. Our study demonstrates that in the face of a leaky urothelium, urinary K+ is the main determinant of afferent hyperexcitability, organ hyperactivity and pain. These findings support the notion that voiding symptoms and pain seen in forms of cystitis that coexist with urothelial barrier dysfunction could be alleviated by cutting urinary K+ levels.